MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL PEMBELAJARAN BERMAIN PERAN PADA SISWA KELAS VI SEKOLAH DASAR - Salim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is the low of activity and student achievement which its development is less encouraging. Therefore this research aimed to overcome the two problems. This research is a class action research with grade VI students as research subject. From the result of the research, it is known that the use of role playing learning model can improve student learning outcomes in civic education learning in cycles I as much as 2 students (25%) from 8 students, cycle II 6 students (75%), from 8 students, and cycle III all students complete (100%).